Entrepreneurship in post-conflict countries: a literature review - Alexandra Moritz; Joern H. Block; Fuad Morina (Review of Managerial Science, 2023)
Many countries are in a state of post-conflict, a situation where an armed conflict between countries or within a country has just come to an end. Such countries are typically poor and characterized by political instability, economic problems and social unrest. Entrepreneurship is considered crucial for such countries as a driver of economic recovery and peacebuilding. However, the exact role and effect of entrepreneurship in a post-conflict context is not well understood and an integrative perspective is needed. Our study reviews the fragmented knowledge on entrepreneurship in post-conflict countries. We structure the literature into four distinct categories ( when and where , who and why, how , and impact ) and develop an integrative conceptual model. Our review reveals research gaps and suggests directions for future research on entrepreneurship in post-conflict countries. Our study also helps policy-makers to design an effective entrepreneurship policy considering the specific requirements of post-conflict contexts.
Keywords: M13; O43; P45; 650; Entrepreneurship; Post-conflict country; Peacebuilding; Economic recovery; Systematic literature review